Validation of the Slovakian version of Boston carpal tunnel syndrome questionnaire (BCTSQ) - Ulbrichtová, Romana; Jakušová, Viera; Švihrová, Viera; Dvorštiaková, Barbora; Hudečková, Henrieta (Acta Medica, 2019)
INTRODUCTION: The most common occupational disease is carpal tunnel syndrome. The aim of this study was to translate and validate the Slovakian version of BCTSQ. METHODS: The original questionnaire was translated into the Slovakian language by two expert translators. Cronbach's alpha coefficient was used to analyze the internal consistency of the questionnaire. Construction validity was evaluated by using Pearson's correlation coefficient and Spearman's rank correlation. The results were processed in the statistical program SPSS 24. The level of significance p > 0.05 was considered significant. To analyze the validity, a factor analysis of the BCTSQ and the correlation between BCTSQ and SF-36 were obtained. RESULTS: A total of 32 employees at risk of local muscular overload completed the BCTSQ and Health Questionnaire SF-36. Cronbach's alpha for SSS was >0.8. The alpha coefficient for FSS was >0.9. The Pearson's coefficient and Spearman's rank correlation was >0.9 for each domain. Cronbach's alpha for SF-36 was >0.7 and the Pearson's coefficient and Spearman's rank correlation was >0.6 and p-values <0.001. CONCLUSIONS: The questionnaire has sufficient reliability, validity and can be a suitable tool for the evaluation of subjective response of employees at the risk of local muscular overload, as well as of patients with carpal tunnel syndrome.
Keywords: diagnostické sebehodnocení; dospělí; mužské pohlaví; Adult; lidé; syndrom karpálního tunelu; překlady; Carpal Tunnel Syndrome; Male; Slovakia; Middle Aged; ženské pohlaví; lidé středního věku; Humans; Female; Diagnostic Self Evaluation; Slovenská republika; Translations